Barrett's esophagus analysis using infinity Restricted Boltzmann Machines - Passos, Leandro A.; de Souza, Luis A.; Mendel, Robert; Ebigbo, Alanna; Probst, Andreas; Messmann, Helmut; Palm, Christoph; Papa, João Paulo [UNESP] (Elsevier, 2019)
The number of patients with Barret's esophagus (BE) has increased in the last decades. Considering the dangerousness of the disease and its evolution to adenocarcinoma, an early diagnosis of BE may provide a high probability of cancer remission. However, limitations regarding traditional methods of detection and management of BE demand alternative solutions. As such, computer-aided tools have been recently used to assist in this problem, but the challenge still persists. To manage the problem, we introduce the infinity Restricted Boltzmann Machines (iRBMs) to the task of automatic identification of Barrett's esophagus from endoscopic images of the lower esophagus. Moreover, since iRBM requires a proper selection of its meta-parameters, we also present a discriminative iRBM fine-tuning using six meta-heuristic optimization techniques. We showed that iRBMs are suitable for the context since it provides competitive results, as well as the meta-heuristic techniques showed to be appropriate for such task.
Keywords: Barrett's esophagus; Deep learning; Infinity Restricted Boltzmann Machines; Meta-heuristics